Epstein-Barr virus associated lymphoepithelial carcinoma of the parotid gland; a clinicopathological report of three cases - Noppadol Larbcharoensub (2018)
Lymphoepithelial carcinoma is a relatively uncommon malignant tumor of the salivary gland demonstrating malignant epithelial cells with dense lymphoid stroma. The authors report three cases of lymphoepithelial carcinoma associated with Epstein-Barr virus of the right parotid gland with clinically presenting as painless, gradual enlargement of the preauricular mass. The histopathologic examination of the parotid gland is characterized by malignant epithelial cells with dense lymphoid stroma. Immunohistochemical stains show positive reactivity to cytokeratin and p53 in malignant epithelial cells. In situ hybridization of the Epstein-Barr virus-encoded Ribonucleic acid shows positivity in malignant epithelial cells. Clinical and pathologic features with relevant literatures are discussed. These are the first reported cases of primary parotid lymphoepithelial carcinoma associated with Epstein-Barr virus infection in Thailand and Southeast Asia.